Chard (Beta vulgaris var. cicla L.) production in hydroponic and aquaponic systems - Ruiz-Velazco, Javier M. J.; de la Paz-Rodriguez, Griselda; Hernandez-Llamas, Alfredo; Estrada-Perez, Nallely (Ecosistemas y Recursos Agropecuarios, 2024)
Hydroponics is the technology of soil-less agriculture, in which plants are grown in an aquatic environment. While aquaponics is a fast-growing food production system that integrates hydroponics with aquaculture (fish farming). The objective of this study was to compare the production of chard (Beta vulgaris var. cicla L.) using a typical hydroponic system and an aquaponic system for tilapia (Oreochromis niloticus) production in a greenhouse. Six independent recirculation systems were used to test production by triplicate. Simple linear regression analysis showed that leaf production rate differed significantly between systems (p < 0.05), where the hydroponic trial produced 3.46 leaves week-1 and the aquaponic trial 1.53 leaves week-1. Plant biomass increased by 53.91 g week-1in the hydroponic and 38.24 g week-1 in the aquaponic treatment, although these production rates did not differ significantly (p > 0.05). No significant differences were detected in the concentrations of ammonium (NH4+), nitrite (NO2-), and phosphate (PO4+) between the treatments; however, significant differences were found for nitrate (NO3-) between the systems (p < 0.05). Chard production in the hydroponic system was higher than in the aquaponic system in terms of leaf number and biomass.
Keywords: Biomass; nutrients; plants; tilapia; recirculation